2017
DOI: 10.12973/ejmste/81548
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Wikis and a LINE Messaging App in Flipped Classrooms

Abstract: The aim of this research is to identify students' perception of the utilization of wikis, LINE, and flipped teaching strategies in a Research Methodology course at a university in Taiwan. Q-methodology, a combination of qualitative and quantitative research, was employed for this study, and sixteen participants were asked to rank-order 30 statements related to the integration of wikis and LINE in a flipped classroom. Correlation, a centroid factor analysis, and judgmental rotation were used to identify the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…It was evident from the feedback received from the teachers, the experts, and the learners in the experimental group that the social media and design thinking-integrated pedagogy was helpful to both the teaching and learning processes. In congruence with the views of researchers such as Alabdulkareem (2015), Bosch (2009), Chen and Chen (2017), Shih et al. (2015) and Madge et al.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…It was evident from the feedback received from the teachers, the experts, and the learners in the experimental group that the social media and design thinking-integrated pedagogy was helpful to both the teaching and learning processes. In congruence with the views of researchers such as Alabdulkareem (2015), Bosch (2009), Chen and Chen (2017), Shih et al. (2015) and Madge et al.…”
Section: Discussionsupporting
confidence: 54%
“…Some studies have also been carried out on learners’ use of instant messaging platforms like Line App. It is important to first note that Line App’s use in Taiwan is more common among smartphone users, and is more popular than Facebook, YouTube, WeChat and Instagram (Chen and Chen, 2017). This suggests the need to focus more attention on how this App is being used for educational purposes, especially among learners.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid making similar mistakes, we recommended that each video be limited to six minutes and all combined video segments be no more than 20-25 min. With this principle applied, Chen and Chen (2018) confirmed that the assigned workload was bearable for the students in their flipped research methodology course.…”
Section: Contribution Of Systematic Reviewsmentioning
confidence: 68%
“…Literature on Q methodology typically describes the process in three to seven steps. Those using fewer steps combine steps such as defining the concourse and deriving Q sample items from the concourse into one step (Chen and Chen 2018). While the number of steps differs, the generally accepted approach remains the same.…”
Section: Background On Q Methodologymentioning
confidence: 99%